Seismic Anisotropy and Its Impact on Imaging the Shallow Alpine Fault: An Experimental and Modeling Perspective. Issue 8 (30th July 2020) - Adam, Ludmila; Frehner, Marcel; Sauer, Katrina; Toy, Virginia; Guerin‐Marthe, Simon
Abstract: The transpressional Alpine Fault in New Zealand has created a thick shear zone with associated highly anisotropic rocks. Low seismic velocity zones and high seismic reflectivity are recorded in the Alpine Fault Zone, but no study has explored the underlying physical rock parameters of the shallow crust that control these observations. Protomylonites are the volumetrically dominant lithology of the fault zone. Here we combine experimental measurements of P ‐wave speeds with numerical models of elastic wave anisotropy of protomylonite samples to explore how the fault zone can be seismically imaged. Numerical models that account for the porosity‐free real samples' fabric elastic tensors from electron backscatter diffraction (EBSD) are calculated by MTEX and a finite element model (FEM), while microfractures are modeled with differential effective medium (DEM) theory. At effective pressures representative of the Alpine Fault brittle zone, experimental wave speeds are lower than those predicted by MTEX/FEM. A possible DEM model suggests that a combination of random and aligned microfractures with aspect ratios increasing with pressure can explain the experimental wave speeds for pressures <70 MPa. Such microporosity in the form of foliation‐ and mica basal plane‐parallel microfractures and grain boundaries is validated with synchrotron X‐ray microtomography and transmission electron microscopy (TEM) images. Finally, by modeling anisotropy of seismic reflection coefficients with angle of incidence, we demonstrate that the high reflectivity and low‐velocity zone (LVZ) observed at the Alpine Fault can only be explained if this microporosity is accounted for throughout the brittle fault zone, even at depths of 7–10 km. Key Points: By combining elastic wave models and laboratory data of Alpine Fault protomylonites, we show the effects of mineral anisotropy and fractures Microstructures imaging and numerical modeling confirm open grain boundaries and (micro)fractures at all depths within the brittle regime These combined structural features explain field observations of high seismic reflectivity and low velocities within the Alpine Fault